Memahami Gerakan Islam Transnasional (Studi Kasus di Indonesia, Brunei, dan Thailand) - Zaeni, Akhmad; Zainuri, Zainuri (Indonesian Journal Publisher, 2023)
This article aims to understand the transnational Islamic movement with a focus on three countries: Indonesia, Brunei, and Thailand. Transnational Islamic movement refers to the flow and influence of Islam that transcends national borders and has significant impacts on the social, political, and religious developments in the involved countries. This case study will discuss the key characteristics of the transnational Islamic movement in Indonesia, Brunei, and Thailand, as well as the factors influencing its development. Additionally, the article will also analyze how this movement plays a role in shaping the Muslim identity in these three countries. The research methods employed in this article are descriptive and comparative analysis. Data is obtained through literature studies and document reviews. The research findings indicate that the transnational Islamic movement in Indonesia, Brunei, and Thailand exhibits different characteristics depending on the respective countries' histories, cultures, and political situations. Factors such as migration, social media, financial support, and political issues play crucial roles in the development of this movement. In conclusion, the transnational Islamic movement has significant impacts within the contexts of Indonesia, Brunei, and Thailand.